SOSIALISASI APLIKASI CHATBOT BERBASIS ANDROID UNTUK GURU SD IMMANUEL JAKARTA BARAT - Mawardi, Viny Christanti; Orlando, Fundroo; Lie, Nadia Natha (LPPM UPN Veteran Jakarta, 2024)
Many teaching and learning methods have been developed by associating the use of various current technologies in order to increase enthusiasm and motivation in teaching and learning activities. Immanuel Elementary School has developed teaching and learning methods using Android-based applications. The Android-based application itself is an application compiled using a programming language that can be accessed by anyone, and at any time, with or without restrictions. This socialization aims to increase knowledge about the use of Android-based applications. Knowledge of the use of Android-based applications needs to be improved so that it can assist users in completing work, making most or all of the work more efficient. Increased knowledge in using Android-based applications can also be a separate medium or means of entertainment for users for exploring something new. In socializing the Android-based Chatbot application for Immanuel Elementary School Teachers, two activities were carried out, namely guiding Immanuel Elementary School teachers in the application installation process and direct demonstrations in using the application. The result of this activity is the successful installation of the Android-based Chatbot application. Based on a survey filled out by 17 respondents who are Immanuel Elementary School teachers, 100% of teachers agree that the Android-based Chatbot application is easy to use, easy to understand, and can provide new experiences in the teaching and learning process. The results obtained from data processing of all indicators are participants agree that using this android application is easier and has an appropriate appearance. In addition, the implementation of the training has provided an increase in teacher knowledge of the meaning of chatbots and their uses.